The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1533033820980089
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Laser Ablation After Excisional Vacuum-Assisted Breast Biopsy for Small Malignant Breast Lesions: Preliminary Results

Abstract: Background: The purpose of this preliminary study is to evaluate the feasibility of the excisional ultrasound (US) guided vacuum-assisted breast biopsy (VAE), followed by US-guided Laser Interstitial Thermal Therapy (LITT) in the treatment of unifocal ductal breast carcinomas ≤ 1 cm and estimate the ablation rate analyzing the final histopathological results after subsequent surgical excision. Methods: In a single session 11 female patients with unifocal less than a centimeter breast cancer underwent 2 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Ablation techniques using thermal energy can complement VABB. In a study that reported 11 cases treated with VABB combined with laser ablation, 90% of the treated patients did not show residual tumors after surgical excision [ 20 ]. In a study using a novel breast lesion excision system that combined radiofrequency with VABB, complete excision was possible for 95.8% of subcentimeter breast cancers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ablation techniques using thermal energy can complement VABB. In a study that reported 11 cases treated with VABB combined with laser ablation, 90% of the treated patients did not show residual tumors after surgical excision [ 20 ]. In a study using a novel breast lesion excision system that combined radiofrequency with VABB, complete excision was possible for 95.8% of subcentimeter breast cancers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that all malignant masses present more than one characteristic of malignant masses; moreover, some benign masses also show malignant signs such as microcalcification, which may be caused by secondary calcification in inflammatory lesions, so careful screening should be conducted. Although two-dimensional ultrasonography has many advantages, it needs to be supplemented by other methods to confirm the nature of masses due to the fact that the malignant masses have unclear morphological characteristics in the early-stage [17][18][19][20]. The advancing of ultrasound technology allows for a wide application of Color Doppler in numerous diseases; this approach has a high sensitivity to blood flow and can reflect the the hemodynamics of the lesions, with a promising clinical application prospect.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1990s, vacuum-assisted breast bi- opsy (VABB) has become increasingly popular due to its high diagnostic efficiency and the ability to treat benign neoplasms of acceptable size as well as minimal (up to 1.0 cm) carcinomas [11,12]. At the same time, negative aspects of VABB are also known, in particular, a relatively high (up to 9.0%) frequency of false negative results, incomplete removal of high-risk lesions, and the impossibility of assessing the margins of the lesion [11,13].…”
Section: Introductionmentioning
confidence: 99%